The science of agriculture : - Herren, Ray V (Thomson/Delmar Learning, 2007)
This book concentrates on the scientific principles of the central components of the agricultural industry. The production of plants and animals in central to fulfilling the need foor food and fibre. Areas such as the environment, food safety, and the future of agriculture are adressed